Scotland, Darien and the Atlantic World, 1698-1700 - Orr, Julie (Julie M.) (Edinburgh University Press, 2018)
"This book synthesises the rare indigenous voice with newly discovered archival sources in Spain, Jamaica and the United States. The result is a new and expanded chronicle of the Scottish Panamanian initiative. It broadens what we know about the Company of Scotland beyond British history and into its rightful place in the saga of the multinational, tumultuous seventeenth-century Atlantic world. Julie Orr offers an in-depth analysis of the complex sociopolitics into which the Scots recklessly inserted themselves through their choice of Darien for settlement. Entanglement with slave-trading interests; the trial of five expedition participants in Spain; the dispatch of Admiral Benbow to the Caribbean with offers of assistance to Spanish governors; the activities of the Scottish spy Walter Herries; and the unintended diaspora of deserters, prisoners and survivors -all are afforded their rightful place in the story of Scotland's attempt to establish a trading colony on the isthmus of Panama." --